Gut microplastics of two non-native freshwater fish species, Geophagus altifrons and Cichla orinocensis, in Singapore reservoirs - Xue Shen Teo; Kean Sim Lai; Jeffrey T. B. Kwik; Maxine A. D. Mowe; Darren C. J. Yeo (Aquatic Ecology, 2026)

Corn Starch/Soybean Wax Double Coated Biochar-based Controlled-release Nitrogen Fertilizer: Water Retention, Release Kinetics and Okra Growth - I. J. X. Yong; I. A. W. Tan; D. H. H. Sim; L. L. P. Lim (Water, Air, & Soil Pollution, 2026)

Diverse prokaryotic strategies associated with soil organic matter priming - M. Waibel; E. Paterson; T.E. Freitag; F. Abram; P.E. Hedley; J. Morris; L.J. Robinson; A. Sim; B. Thornton; F.P. Brennan (Applied Soil Ecology, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Prospective life cycle assessment of climate and biodiversity impacts of meat‐based and plant‐forward meals: A case study of Indonesian and German meal options - Sandra G. Marquardt; P. James Joyce; Giles Rigarlsford; Mariska Dötsch‐Klerk; Kathelijn van Elk; Jonathan Doelman; Vassilis Daioglou; Mark A. J. Huijbregts; Sarah Sim (Journal of Industrial Ecology, 2024)
The emerging field of prospective life cycle assessment (pLCA) offers opportunities for evaluating the environmental impacts of possible future consumption shifts. One such shift involves a transition from meat‐based to plant‐forward diets, acknowledged to mitigate environmental impacts of the food system under present day conditions. Current diets are often meat intensive (“meat‐based”), whilst “plant‐forward” diets include mainly plant‐based foods, encompassing flexitarian, vegetarian, and vegan diets. Here we illustrate the application of pLCA in a case study of meal options, implementing shared socio‐economic pathway scenarios in the LCA background system to represent future production conditions. We assess the climate footprints and land‐based biodiversity footprints of a typical meat‐based meal in Germany and Indonesia compared to a plant‐forward meal in both countries (i.e., four meals), now and in 2050. Our findings show that the plant‐forward alternative maintains a lower impact per serving in all future scenarios. At the same time, the reduction in impact for the meat‐based meals is more pronounced in future scenarios due to shifts in the agricultural system. Our findings highlight the importance of supply‐side measures to produce lower‐impact ingredients, complementing demand‐side interventions to reshape food consumption. Results are further evaluated in cultural and nutritional contexts, highlighting the practical decision‐making constraints faced by consumers. We find potential “leakage” effects in calories and nutrition when choosing a lower‐impact, plant‐forward meal. These leakage effects should be considered in future studies seeking to evaluate the environmental implications of meal substitutions in the context of broader dietary requirements.

Land use diversification may mitigate on‐site land use impacts on mammal populations and assemblages - Koen J. J. Kuipers; Sarah Sim; Jelle P. Hilbers; Stefanie K. van den Berg; Melinda M. J. de Jonge; Krista Trendafilova; Mark A. J. Huijbregts; Aafke M. Schipper (Global Change Biology, 2023)
Land use is a major cause of biodiversity decline worldwide. Agricultural and forestry diversification measures, such as the inclusion of natural elements or diversified crop types, may reduce impacts on biodiversity. However, the extent to which such measures may compensate for the negative impacts of land use remains unknown. To fill that gap, we synthesised data from 99 studies that recorded mammal populations or assemblages in natural reference sites and in cropland and forest plantations, with or without diversification measures. We quantified the responses to diversification measures based on individual species abundance, species richness and assemblage intactness as quantified by the mean species abundance indicator. In cropland with natural elements, mammal species abundance and richness were, on average, similar to natural conditions, while in cropland without natural elements they were reduced by 28% and 34%, respectively. We found that mammal species richness was comparable between diversified forest plantations and natural reference sites, and 32% lower in plantations without natural elements. In both cropland and plantations, assemblage intactness was reduced compared with natural reference conditions, but the reduction was smaller if diversification measures were in place. In addition, we found that responses to land use were modified by species traits and environmental context. While habitat specialist populations were reduced in cropland without diversification and in forest plantations, habitat generalists benefited. Furthermore, assemblages were impacted more by land use in tropical regions and landscapes containing a larger share of (semi)natural habitat compared with temperate regions and more converted landscapes. Given that mammal assemblage intactness is reduced also when diversification measures are in place, special attention should be directed to species that suffer from land use impacts. That said, our results suggest potential for reconciling land use and mammal conservation, provided that the diversification measures do not compromise yield.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Kappa opioid receptors mediate an initial aversive component of paclitaxel-induced neuropathy - Julie A. Meade; Y. Alkhlaif; K. M. Contreras; S. Obeng; W. Toma; L. J. Sim-Selley; D. E. Selley; M. I. Damaj (Psychopharmacology, 2020)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

∆9-Tetrahydrocannabinol-dependent mice undergoing withdrawal display impaired spatial memory - Laura E. Wise; Stephen A. Varvel; Dana E. Selley; Jason M. Wiebelhaus; Kelly A. Long; Lisa S. Middleton; Laura J. Sim-Selley; Aron H. Lichtman (Psychopharmacology, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Glycosaminoglycans from earthworms (Eisenia andrei) - A-Rang Im; Youmie Park; Joon-Soo Sim; Zhenqing Zhang; Zhenling Liu; Robert J. Linhardt; Yeong Shik Kim (Glycoconjugate Journal, 2010)

Identification of high-mannose and multiantennary complex-type N-linked glycans containing α-galactose epitopes from Nurse shark IgM heavy chain - David J. Harvey; Max Crispin; Beryl E. Moffatt; Sylvia L. Smith; Robert B. Sim; Pauline M. Rudd; Raymond A. Dwek (Glycoconjugate Journal, 2009)

Variation of acharan sulfate and monosaccharide composition and analysis of neutral N-glycans in African giant snail (Achatina fulica) - Youmie Park; Zhenqing Zhang; Tatiana N. Laremore; Boyangzi Li; Joon-Soo Sim; A-Rang Im; Mi Young Ahn; Yeong Shik Kim; Robert J. Linhardt (Glycoconjugate Journal, 2008)

Does chemical composition of individual Scots pine trees determine the biodiversity of their associated ground vegetation? - Glenn R. Iason; Jack J. Lennon; Robin J. Pakeman; Vera Thoss; Joan K. Beaton; David A. Sim; David A. Elston (Ecology Letters, 2005)
Despite plant secondary metabolites being major determinants of species interactions and ecosystem processes, their role in the maintenance of biodiversity has received little attention. In order to investigate the relationship between chemical and biological diversity in a natural ecosystem, we considered the impact of chemical diversity in individual Scots pine trees ( Pinus sylvestris ) on species richness of associated ground vegetation. Scots pine trees show substantial genetically determined constitutive variation between individuals in concentrations of a group of secondary metabolites, the monoterpenes. When the monoterpenes of particular trees were assessed individually, there was no relationship with species richness of associated ground flora. However, the chemical diversity of monoterpenes of individual trees was significantly positively associated with the species richness of the ground vegetation beneath each tree, mainly the result of an effect among the non‐woody vascular plants. This correlation suggests that the chemical diversity of the ecosystem dominant species has an important role in shaping the biodiversity of the associated plant community. The extent and significance of this effect, and its underlying processes require further investigation.

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Establishing the Link between Ammonia Emission Control and Measurements of Reduced Nitrogen Concentrations and Deposition - Mark A. Sutton; Willem A. H. Asman; Thomas Ellermann; J. A. Van Jaarsveld; Karin Acker; Viney Aneja; Jan Duyzer; Laszlo Horvath; Sergey Paramonov; Marta Mitosinkova; Y. Sim Tang; Beat Achermann; et al. (Environmental Monitoring and Assessment, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Analysis of 15 primary open-angle glaucoma families from Australia identifies a founder effect for the Q368STOP mutation of myocilin - Paul N. Baird; Jamie E. Craig; Andrea J. Richardson; Maree A. Ring; Pamela Sim; Sue Stanwix; Simon J. Foote; David A. Mackey (Human Genetics, 2003)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Small (SK Ca ) Ca 2+ -activated K + channels in cultured rat hippocampal pyramidal neurones - A. A. Selyanko; J. A. Sim; D. A. Brown (Pflügers Archiv - European Journal of Physiology, 1998)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)